PEMBERDAYAAN PENDIDIKAN KEWIRAUSAHAAN DI PONDOK PESANTREN ULUMUL QURAN BOJONGSARI DEPOK - Wagola, Basri M. (Tawazun: Jurnal Pendidikan Islam, 2018)
Unemployment and poverty are classic problems and become homework for Indonesia. Because unconsciously, they direct students to become workers. Whereas employment opened by the government is not commensurate with graduates. Entrepreneurship education is expected to be a solution so that graduates of general education institutions and pesantren can be independent and can open jobs for the wider community. This research was conducted at Ulumul Qur'an Islamic Boarding School. From this study found several conclusions, namely the concept of entrepreneurship education in PPUQ is Islamic-based entrepreneurship with the selection of students with the studying by doing method. while the entrepreneurial contribution to pesantren is to develop the economic independence of pesantren, strengthen pesantren economy and create cadres of educators with entrepreneurial knowledge.